Heidi solved the equation 3(x + 4) + 2 = 2 + 5(x – 4). Her steps are below: 3x + 12 + 2 = 2 + 5x – 20 3x + 14 = 5x – 18 14 = 2x – 18 32 = 2x 16 = x Use the drops-downs to justify how Heidi arrived at each step. Step 1: Step 2: Step 3: Step 4: Step 5:

Respuesta :

Answer:

see below

Step-by-step explanation:

3(x + 4) + 2 = 2 + 5(x – 4)

Distribute using the distributive property

3x + 12 + 2 = 2 + 5x – 20

Combine like terms  (simplify)

3x + 14 = 5x – 18

Subtract 3x from each side using the subtraction property of equality

14 = 2x – 18

Add 18 to each side using the addition property of equality

32 = 2x

Divide each side by 2 using the division property of equality

16 = x

Answer:

3(x + 4) + 2 = 2 + 5(x – 4)Distribute using the distributive property 3x + 12 + 2 = 2 + 5x – 20 Combine like terms  (simplify)3x + 14 = 5x – 18Subtract 3x from each side using the subtraction property of equality14 = 2x – 18Add 18 to each side using the addition property of equality32 = 2xDivide each side by 2 using the division property of equality16 = x

Step-by-step explanation: